Photodynamic therapy for malignant tumours of the ampulla of Vater. Issue 6 (June 1995) - Abulafi, A M; Allardice, J T; Williams, N S; van Someren, N; Swain, C P; Ainley, C
Abstract : Ten patients with ampullary carcinoma, not suitable for surgery, were treated with endoscopic photodynamic therapy (PDT) to evaluate the feasibility and safety of treatment. Patients received 4 mg kg-1 of haematoporphyrin derivative intravenously. Two days later, a duodenoscopy was performed and red (630 nm) light delivered to the tumour at fixed energy densities of 50 J or 200 J cm-1 per application, depending on the type of optical fibre used. The tumours were treated by three or four light applications at each session. Treatment was repeated up to five times at intervals of three to six months. The sole complication of PDT was moderate skin photosensitivity, which occurred in three patients. Tumour size was assessed at four to eight weekly intervals. In the absence of macroscopic tumour, biopsy specimens were taken. In three patients with small tumours confined to the ampulla, remission was obtained for periods ranging from eight to 12 months. In a further four patients with small tumours bulk was greatly reduced. There was little response in three patients with extensive duodenal involvement. Therefore PDT for ampullary carcinoma is both feasible and safe, and with refinement may prove curative for small tumours.